Nucleotide inclusion in pet food: effect of heat treatment and storage - Russo, Natalia; Candellone, Alessia; Galaverna, Davide; Prola, Liviana (Progress in Nutrition, 2019)
Nucleotide supplementation in pet foods aims to reinforce the immune system and promote intestinal function. Data on alteration of nucleotides during pet food processing are lacking, however. With this study we compared the recovery percentage of nucleotides in dry and canned food after processing and controlled environment storage. Selected dry and canned feed were supplemented with 0.4g/100 g dry matter basis of Prosol petMOD™ (free nucleotide concentrate ) before exposure to high temperature. In detail, the highest temperature applied to dry pet food was 110° C and around 125° C to canned food. The recovery percentage for dry food was 75% at the end of processing and 74% after storage for 12 months versus 43% and 41%, respectively, for canned food.. These results indicate that dietary supplementation with nucleotides to pet food may benefit animal health; however, a  high loss of these semi-essential nutritional components was observed, particularly in the canned pet food.